Analisis Kemampuan Literasi Siswa dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) Materi Statistika di SMAN 1 X Koto Kabupaten Tanah datar - Annisa Syafitri; Villia Anggraini; Lucky Heriyanti Jufri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research was motivated by the low numeracy literacy abilities of students in solving AKM questions on statistics material at SMAN 1 X Koto, Tanah Datar Regency. The aim of this research is to find out how students' numeracy literacy skills are in solving AKM questions on statistics material at SMAN 1 X Koto, Tanah Datar Regency. This type of research is qualitative descriptive research. The research subjects were 26 students in class XE1. The data collection methods used were tests and interviews. Tests are used to see indicators of numeracy literacy abilities while interviews are used to strengthen the results of the tests carried out. The results of this research show that the numeracy literacy skills of students at SMAN 1 40. In the medium category with an average score of 69. However, there are still those who have high literacy skills, namely with an average score of 85.